DEPÓSITOS DE ARGILA ORGÂNICA MOLE – UM EXEMPLO EXTREMO NA BACIA DO RIO BARIGUI - Nascimento, Ney Augusto; Kuster Puppi, Rogério Francisco (Boletim Paranaense de Geociências, 2008)
The Barigui River is a tributary of the Iguaçu River, located at Parana State, Brazil. This river is the main water stream of the Metropolitan Area of Curitiba, Southern Brazil. In the flood plain of the Barigui River final stretch, nearby its delta at the Iguaçu River, very soft organic clay deposits are found. The region suffered until some years ago predatory mining activities of both clay and sand, for construction material purposes. Consequently, a degradation process took place resulting in lack of vegetation, excavation open pits and random materials dump areas. Simultaneously several engineering activities have been installed along the river banks such as the Petrobras Oil Refinery (located at the right bank), the Santa Rita Rural Subdivision, the CIC Sewage Treatment Plant of the State owned company Sanepar, the Bolívia-Brazil Gas Pipeline (Gasbol) and the Rio Bonito Housing Development (all located along the left bank). The flood plain area considered herein is located on the river left bank, encompassing approximately an area of 500 m wide by 1000 m long. This paper describes the geological and geotechnical characteristics of the flood plain area, presenting results of several soil tests. A discussion about some practical experiences, including engineering difficulties and solutions implemented during the construction of the facilities above described, are shown. This paper concludes that even though the local organic clay deposits are very soft and compressible, this natural material of the Barigui River flood plain area presents unique engineering behavior, much more complex than well known problematic soils.